Improvement of a Dynamic Frequency Hopping Optical Code Division Multiple Access System Using Power Control Method - Mazehr Algalbi, Wamidh J. (2009)
In this thesis, adaptive power control method is proposed to improve the performance of dynamic frequency hopping-optical code division multiple access (DFH-OCDMA) communication system. This method is based on solving the near-far problem of power misdistribution among simultaneous users. The DFH-OCDMA has an advantage of supporting more users compared to other OCDMA techniques such as Hadamard code, modified quadratic congruence code, modified frequency hopping code, and fast frequency hopping system. Nevertheless, the bit error rate (BER) was found to deteriorate rapidly with a slight change of received power compared to the other techniques. With the change of the received power (i.e. from -10 dBm to -12 dBm), the BER could be degraded from 10-9 to 10-6. This phenomenon is strongly related to nearfar problem, where users at longer path lengths will suffer higher BER compared to users at shorter path lengths. The unequal power distribution among users leads to unequal performance for them. This may cause to not all users can be supported in the transmission system. Therefore, this study is aimed to search for a solution to increase the number of users under the DFH-OCDMA system with near-far problem. A distributed power control algorithm was proposed to enhance the performance of the system and this was done by considering all possible noises such as the multiple access interference, phase induced intensity noise, and shot noise. The performance of the system was also observed at different issues of fibre impairments, including fibre attenuation, and optical components. The results gathered from the simulations showed that BER and signal-to-noise-ratio (SNR) for each user were significantly improved after using the power control. In specific, it is observed that the best capacity increased was 51% when the random path lengths for 110 users was between 1 to 40 km. Thus, the power control method is proven as an important enhancement to DFH-OCDMA performance. Moreover, the number of users increased in the DFH-OCDMA system with power control was 56 users while at prime code OCDMA and time hopping, only 20 users increment with power control. This result therefore shows better improvement of capacity in DFH-ODCMA compared to other Power Controlled-OCDMA.